Profile of consumers and their partners of a perinatal and infant mental health (PIMH) service in Australia. (4th September 2017) - Coates, Dominiek; Saleeba, Christine; Howe, Deborah
Abstract: The perinatal period is a time of great vulnerability for many women, in particular those with a range of psychosocial vulnerabilities and mental health risk factors. This paper outlines the psychosocial and mental health profile of consumers and their partners of a perinatal and infant mental health (PIMH) service in Australia. To establish the consumer profile, we analysed client vulnerabilities and demographical information maintained over a 6‐year period for 406 consumers. Consumer information, including mental health problems, psychosocial vulnerabilities and demographical information, was entered into a standalone database by the allocated clinicians upon service allocation and throughout treatment. The women accepted by PIMH presented with an average of nine different vulnerabilities. Frequently endorsed risk factors included depression (72.66%), anxiety (71.43%), comorbid depression and anxiety (58.13%), self‐harm (past, 7.88%, present, 16.26%), a history of family mental health issues (39.66%), childhood trauma (57.88%), limited support (68.84%), relationship conflict with partners (38.92%) and financial stress (47.29%). The women's partners also presented with a range of vulnerabilities, in particular childhood trauma (34.11%) and mental health issues (30.81%). This study contributes to our understanding of the profile of vulnerable women in the perinatal period, and in particular contributes to the literature by highlighting that in addition to depression, anxiety, self‐harm and trauma are also significant in PIMH service delivery.